Correlation Analysis of Flag Leaf with Yield in Several Rice Cultivars - Rahman, Md Asadur; Haque, ME; Sikdar, B; Islam, Md Asadul; Matin, Muhammad Nurul (Journal of Life and Earth Science, 2014)
The uppermost leaf below the panicle is the flag leaf that provides the most important source of photosynthetic energy during reproduction and grain filling, thereby has great impact in panicle development and grain yield in rice. In the present investigation in order to explore the relationship between grain yield and flag leaf parameters, yield composition, length and width of the flag leaf, and panicle length were measured in some rice cultivars. Statistical analysis indicated that flag leaf length was positively correlated with panicle length for the studied cultivars demonstrating higher grain yield. Chlorophyll measurement indicated that flag leaf contained more chlorophyll than penultimate leaf. Yield of all the cultivars upon excision of flag leaf was also compared. Removal of flag leaf led to a decline in the seed-setting rate which eventually reduced the grain yield. Besides this, variable pollen viability was also noticed in the different cultivars. DOI: http://dx.doi.org/10.3329/jles.v8i0.20139 J. Life Earth Sci., Vol. 8: 49-54, 2013